2005
DOI: 10.1212/01.wnl.0000167552.79769.b3
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 gene in Parkinson disease

Abstract: The results support the prior suggestion that LRRK2 mutations cause PD. The disease in the families reported here presents a phenotype indistinguishable from typical PD. All three families demonstrate a very variable age at onset that is not explained by APOE genotypes. The common coding variations in the LRRK2 gene neither constitute strong PD risk factors nor modify the age at onset; however, the possibility of a modest risk effect remains to be assessed in large datasets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
113
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(119 citation statements)
references
References 20 publications
6
113
0
Order By: Relevance
“…These frequencies are in substantial agreement with those reported in the only two previous studies of comparable size, which comprehensively screened the LRRK2 gene, and found mutations in 3/23 and 6/34 families, respectively (13% and 17%). 9,18 ADPD represents a relevant fraction of the whole population of PD. According to the results of this and the previous studies, 9,18 LRRK2 mutations are clearly the most frequent cause of PD known so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These frequencies are in substantial agreement with those reported in the only two previous studies of comparable size, which comprehensively screened the LRRK2 gene, and found mutations in 3/23 and 6/34 families, respectively (13% and 17%). 9,18 ADPD represents a relevant fraction of the whole population of PD. According to the results of this and the previous studies, 9,18 LRRK2 mutations are clearly the most frequent cause of PD known so far.…”
Section: Discussionmentioning
confidence: 99%
“…11 To date, five LRRK2 missense mutations associated with autosomal dominant PD (p.R1441C, p.R1441G, p.Y1699C, p.G2019S, and p.I2020T) 9,10,12 -15 are considered definitely pathogenic on the basis of clear cosegregation with disease in large pedigrees and absence in controls. The evidence for cosegregation with PD is limited for another two mutations found in small families (p.L1114L and p.I1122 V), 9,16 whereas it is lacking for four additional mutations because DNA from relatives was unavailable (p.I1371 V and p.R1441 H), 17,18 or because the mutation was identified in single sporadic PD cases (IVS31 þ 3A4G and p.M1869 T); 16,17 the pathogenic role of these last six mutations remains therefore uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Two Caucasian probands were assessed both by the direct sequencing approach and by resequencing microarray analysis. 13 To evaluate the molecular epidemiology of LRRK2 variants identified by the resequencing of LRRK2, DNA samples from index patients from 89 Ad-PD families and 73 sPD patients, and samples from 233 Japanese normal controls were further analyzed (Table 1b). All the genomic DNA samples were obtained with the written informed consent of the subjects, and this research project was approved by the Institutional Review Board of the University of Tokyo.…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
“…This mutation is very frequent in PD and extremely rare in controls, 5 -8,12 and it cosegregates with PD in large families. 6,8,13 The G2019 residue is extremely conserved in LRRK2 homologs and the mutation increases the kinase activity of the protein. 14 However, the prevalence of G2019S is population specific: very rare in Asia, 15 low in Northern Europe, 8 and high in Italy, 12 Spain 16 and Portugal.…”
mentioning
confidence: 99%
“…A few carriers of the G2019S mutation also carry parkin gene mutations. 1,13 Digenic or polygenic inheritance could explain the lack of a Mendelian pattern of inheritance in most PD families. We do not currently understand the mechanisms underlying the large variability in onset age and other clinical features, observed even among the members of the same G2019S family; other factors must modify the expression and progression of the disease.…”
mentioning
confidence: 99%